Knockdown of INPP5K compromises the differentiation of N2A cells - Manzolillo, Annamaria; Gresing, Lennart; Hübner, Christian A.; Franzka, Patricia (Frontiers in Molecular Neuroscience, 2024)
Inositol polyphosphate 5-phosphatase K (INPP5K) also known as SKIP (skeletal muscle and kidney enriched inositol phosphatase) is a cytoplasmic enzyme with 5-phosphatase activity towards phosphoinositides (PIs). Mutations in INPP5K are associated with autosomal recessive congenital muscular dystrophy with cataracts and intellectual disability (MDCCAID). Notably, the muscular dystrophy is characterized by the hypoglycosylation of dystroglycan. So far, the underlying mechanisms are only partially understood. Here, we show that INPP5K expression increases during brain development. Its knockdown in the neuroblastoma-derived cell line N2A impaired their neuronal-like differentiation and interfered with protein glycosylation.